Pendampingan Legalitas Usaha Berbasis Partisipatif untuk UMKM di Dusun Jombangan Santren - Mustajib; Nilam Cahya, Nur Anisa (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Business legality assistance is a strategic step to enhance the competitiveness and sustainability of Micro, Small, and Medium Enterprises (UMKM), especially in rural areas. This service is carried out in Jombangan Santren Hamlet, Tertek Village, Pare District, Kediri Regency, with the aim of providing understanding and technical assistance to UMKM actors regarding the importance of business legality and the process of registering for a Business Identification Number (NIB) through the Online Single Submission (OSS) application. This activity uses a Participatory Action Research (PAR) approach that emphasizes the active participation of the community in all stages, from problem identification, planning, implementation, to evaluation. The results of the implementation show an increased awareness among UMKM players regarding the importance of business legality, marked by active participation in the socialization process and the success of registering businesses through OSS. This program also has an impact on increasing collaboration among MSME players and optimizing the use of digital technology. These findings reinforce the importance of a participatory mentoring model as an instrument for community economic empowerment based on legality.